AlloRep: A Repository of Sequence, Structural and Mutagenesis Data for the LacI/GalR Transcription Regulators. Issue 4 (22nd February 2016) - Sousa, Filipa L.; Parente, Daniel J.; Shis, David L.; Hessman, Jacob A.; Chazelle, Allen; Bennett, Matthew R.; Teichmann, Sarah A.; Swint-Kruse, Liskin
Abstract: Protein families evolve functional variation by accumulating point mutations at functionally important amino acid positions. Homologs in the LacI/GalR family of transcription regulators have evolved to bind diverse DNA sequences and allosteric regulatory molecules. In addition to playing key roles in bacterial metabolism, these proteins have been widely used as a model family for benchmarking structural and functional prediction algorithms. We have collected manually curated sequence alignments for > 3000 sequences, in vivo phenotypic and biochemical data for > 5750 LacI/GalR mutational variants, and noncovalent residue contact networks for 65 LacI/GalR homolog structures. Using this rich data resource, we compared the noncovalent residue contact networks of the LacI/GalR subfamilies to design and experimentally validate an allosteric mutant of a synthetic LacI/GalR repressor for use in biotechnology. The AlloRep database (freely available atwww.AlloRep.org ) is a key resource for future evolutionary studies of LacI/GalR homologs and for benchmarking computational predictions of functional change. Graphical abstract: Highlights: AlloRep compiles sequence, mutagenesis, and structural data for LacI/GalR proteins. Alignments for > 3000 sequences are grouped by subfamily and sampled in the whole family alignment. AlloRep includes detailed phenotypic and biochemical data on almost 6000 variants. Structural data for 65 proteins are available as residue contact networks. A predicted allosteric position was validated by altering a synthetic repressor.